2022
DOI: 10.3389/fbioe.2022.775676
|View full text |Cite
|
Sign up to set email alerts
|

Performance Monitoring of Anaerobic Digestion at Various Organic Loading Rates of Commercial Malaysian Food Waste

Abstract: Application of anaerobic digestion (AD) has become common in treating palm oil mill effluent in Malaysia; however, employing AD in treating the organic fraction of municipal solid waste (OFMSW), especially food waste, is still scarce. This study aims to characterize the commercial Malaysian food waste (CMFW) and determine its potential as sustainable bioenergy feedstock through biogas production. The sample was digested via the biomethane potential (BMP) test with the variation of organic loading rates (OLRs),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Moreover, the drop in pH value could also be attributed to the long-chain fatty acids (LCFAs) piled up in the system [ 59 ]. The sudden decrease in pH in the system causes the inhibition of the syntrophic bacteria, acetogen and methanogen, hence the unstable system [ 60 ]. The inhibition at OLR 7 g/L/day can be explained by the excess amount of substrate due to a high loading rate, causing insufficient time for hydrolysis in the CSTR reactor [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the drop in pH value could also be attributed to the long-chain fatty acids (LCFAs) piled up in the system [ 59 ]. The sudden decrease in pH in the system causes the inhibition of the syntrophic bacteria, acetogen and methanogen, hence the unstable system [ 60 ]. The inhibition at OLR 7 g/L/day can be explained by the excess amount of substrate due to a high loading rate, causing insufficient time for hydrolysis in the CSTR reactor [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it can be clearly seen that biodigester 2 with 10% whey, exceeds the daily amount of biogas compared to other digesters. After day 15, it appears the maximum production of biogas, this tends to decrease; probably due to solid reduction and ammonia accumulation from protein digestion [14], given that in the last 2 weeks the addition of NaOH was not necessary and probably the ammonia provided the alkalinity to the medium; but since this a critic compound in the toxicity and inhibition of the medium [15], its high concentration inhibit the methanogenesis process. Figure 2 shows the biogas accumulation during the process of digestion to biodigesters 1, 2, 3 and 4.…”
Section: A Biogas Productionmentioning
confidence: 99%
“…In addition, Hanif et al demonstrated the viability of using household food waste, showing that a 72 kW biogas plant could be constructed to produce roughly 630,00 kWh of electricity for 500 households [15]. Further demonstrating the viability of using food waste as feedstock for biogas production in Malaysia, which is crucial for creating a circular economy, a biomethane potential test on food waste using a continuous anaerobic digestion system yields a maximum methane composition of 81% at 1.92 g COD/L [42].…”
Section: Municipal Solid Waste (Msw) Biomassmentioning
confidence: 99%